2022
DOI: 10.31234/osf.io/cvnqm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Backchannel Behavior in Child-Caregiver Video Calls

Abstract: An important step in children’s socio-cognitive development is learning how to engage in coordinated conversations. This requires not only becoming competent speakers but also active listeners. This paper studies children’s use of backchannel signaling (e.g., ”yeah!” or a head nod) when in the listener’s role during conversations with their caregivers via Zoom. While previous work had found backchannel to be still immature in middle childhood, our use of both more natural/spontaneous conversational settings an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 14 publications
0
12
1
Order By: Relevance
“…As a data acquisition method, they capitalized on the recent increase in familiarity and use of online video calls by children -due to Covid-19 pandemic -to record video calls between children and their caregivers at home while playing a simple, intuitive verbal game. In contrast to previous studies, [4] found that children aged 6 to 12 years old produced BC at a rate that was comparable to that of adults.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…As a data acquisition method, they capitalized on the recent increase in familiarity and use of online video calls by children -due to Covid-19 pandemic -to record video calls between children and their caregivers at home while playing a simple, intuitive verbal game. In contrast to previous studies, [4] found that children aged 6 to 12 years old produced BC at a rate that was comparable to that of adults.…”
contrasting
confidence: 99%
“…We investigate children's level of BC mastery in terms of collaborative production and elicitation of BC, using the same corpus of conversations analyzed in [4]. When children are in the listening mode, we measure their ability to react consistently to the speaker's inviting cues.…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation is that we focused only on one aspect of alignment (lexical repetition) which provides a partial view of how interlocutors align to each other multimodally in social interaction (Rasenberg et al, 2020). A more comprehensive investigation would require using child-caregiver corpora that facilitate the study of multimodal face-toface conversations (e.g., Bodur et al, 2021Bodur et al, , 2022.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Besides, the annotation relied primarily on verbal data. In future research, we will extend this work both via automatic labeling to test the scalability of the findings (e.g., Cervone and Riccardi, 2020; and via using corpora that allow for the study of multimodal signaling (e.g., Bodur et al, 2021Bodur et al, , 2022.…”
Section: Future Workmentioning
confidence: 99%